Implementasi Pendidikan Keislaman Dan Kemuhammadiyahan Pada Siswa SMA Muhammadiyah 1 Temanggung - Kurniandini, Sholeh; Fahrub, Abdul Wahab (Universitas Muhammadiyah Yogyakarta, 2023)
The purpose of this study was to determine the implementation of Islamic Education and Muhammadiyah in Muhammadaiyah 1 Temanggung High School students in participating in learning activities. This research uses qualitative research. Informants consisted of class X students and Muhammadiyah 1 Temanggung High School Muhammadiyah subject teachers. Data collection was done by in-depth interviews and observation. The results showed that Muhammadiyah 1 Temanggung High School Muhammadiyah education is carried out through a habituation program, including: 1) Reading the Koran every morning before the teaching and learning process is carried out 2) every Friday there is a spiritual inspiration before the teaching and learning process begins 3) holding Friday prayers in congregation 4) holding taklim assembly activities every Friday 5) memorizing short letters, hadith and daily prayers 6) tapaksuci.